Seroepidemiological study of leptospirosis among the communities living in periurban areas of Sarawak, Malaysia - Thayaparan, Sivapiragasam; Robertson, Ian D; Amaran, Fairuz; Lela, Binti Suut; Gunasekera,, Umanga Chathurani; Mohd Tajuddin, Bin Abdullah (Malaysian Medical Association, 2005)
Introduction: Leptospirosis is endemic to tropical regions of the world and is re-emerging as a new danger to public health in Malaysia. the purpose of this particular study was to determine the common leptospiral serovars present in human communities living around wildlife reserves/disturbed forest habitats. the objective of this study was to estimate the seroprevalence of leptospirosis and finding infecting serovars in villages surrounded habitats where wildlife lives in Sarawak, Malaysia.